223 Sleep Duration and Sleep Quality in Chronic Cannabis Users and Non-Users. (3rd May 2021) - Tse, Caroline; Stewart, Alicia; Ordaz-Johnson, Omar; Herzig, Maya; Gagnon, Jacqueline; Emens, Jonathan; Shea, Steven; Bowles, Nicole
Abstract: Introduction: Cannabis use is on the rise in the United States, with 10% of adults reporting cannabis use in the past 30 days. Users commonly report consuming cannabis to improve sleep despite the lack of research that supports an association between cannabis use and sleep. In this pilot study we sought to examine objective measures of sleep duration and sleep quality among non- and chronic-cannabis users, and any patterns in relation to the time since consumption of cannabis. Methods: Chronic cannabis users (cannabis used 2 or more times/week) and non-users provided up to 2-weeks of actigraphy (ActiGraph wGT3X-BT), worn on the wrist and verified by sleep diary. Chronic cannabis users also reported the date, time, amount, and route of their cannabis use. Mixed-effects models with participant as a random factor were used to examine: 1) the relationship between daily sleep parameters in cannabis non-users vs. users; and 2) the elapsed time between cannabis use and time in bed in chronic cannabis users. Results: Chronic cannabis users (n=6) and non-users (n=7) collectively provided 151 nights of sleep. Participant characteristics (38.5% female; age, 25.8 years ± 4 years; BMI, 23.4 kg/m2 ± 3.4 kg/m2) did not significantly differ between groups. Cannabis use was associated with decreased total sleep time (measured in hours, ß=-0.58, p<0.001) and increased wake after sleep onset (WASO, ß=32.79, p=0.005), but not with the number of awakenings (ß=6.02, p=0.068). Among chronic cannabis users, cannabis use within two hours of bed was associated with increased sleep latency compared to use greater than two hours (ß=6.66, p=0.026). There was no association between time of cannabis use and WASO (p=0.621) or the number of awakenings (p=0.617). Conclusion: In this pilot study of objectively measured sleep, we found that chronic cannabis use compared to non-use is associated with decreased sleep duration of otherwise healthy adults. Cannabis used closer to bedtime is associated with increased sleep latency. Additional studies that are able to assess the mode and dosage of use are needed to further understand the effects of cannabis and its components on sleep. Support (if any): KL2TR002370, AASM, Oregon Institute of Occupational Health Sciences